QOL-24. Evaluating the diagnostic validity & predictive value of the Cerebellar Cognitive Affective Syndrome (CCAS) in pediatric posterior fossa tumour patients. (3rd June 2022) - Hoffmann-Lamplmair, Doris; Leiss, Ulrike; Peyrl, Andreas; Slavc, Irene; Czech, Thomas; Gram, Alexandra; Pletschko, Thomas
Abstract: OBJECTIVE: The present study aimed to examine the extent of deficits associated with the Cerebellar Cognitive Affective Syndrome (CCAS) in patients treated for paediatric posterior fossa tumours (PFT). Furthermore, we wanted to assess its diagnostic validity and predictive value for late sequelae. METHOD: Neuropsychological test data from 56 PFT patients treated at our pediatric neuro-onocology unit (mean age at treatment: seven years; mean age at first neuropsychological examination: nine years) were examined for severity of deficits in the CCAS core domains of executive functions, verbal functions, visuospatial abilities and emotions/behaviour. Patients with CCAS (n=20) were compared to two control groups without the syndrome (PFT patients treated either surgically (n=18) or surgically followed by radio/chemotherapy (n=18)) in terms of long-term neuropsychological and educational outcomes (mean age: 14 years). We also examined risk factors for CCAS development. RESULTS: The results showed mild to severe impairment in at least one CCAS domain in 55 out of 56 patients. Complete CCAS was diagnosed in 35.7% of cases. Seven years after tumour diagnosis, information processing, logical thinking, verbal functions, visuospatial skills and executive functions were more impaired in CCAS patients than in controls. They also needed more special educational support. Information processing speed was equally poor in CCAS patients and in controls treated with chemotherapy/radiotherapy. A significant association was found between risk factors and deficits in information processing speed, but not with the occurrence of CCAS. CONCLUSION: Deficits in the central CCAS features are common in PFT patients, but in varying degrees, suggesting that it is a continuous syndrome rather than a dichotomous one. However, it is problematic that domains such as information processing speed are not included in the diagnosis. External criteria regarding everyday life should be considered in future studies.